2017
DOI: 10.1016/j.ijpddr.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Progressive increase in point mutations associates chloroquine resistance: Even after withdrawal of chloroquine use in India

Abstract: Chloroquine (CQ) is highly effective against P. vivax, due to the rapid spread of CQ resistance in P. falciparum parasites; it is no longer the drug of choice against P. falciparum. This study elucidates the scenario of chloroquine efficacy at times that coincided with a new drug policy and especially assessed the chloroquine resistant molecular markers after withdrawal of chloroquine in Kolkata and Purulia, two malaria endemic zones of West Bengal, India. In vitro CQ susceptibility was tested in 781 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Analysis indicates that 67.1% of samples with CVIET haplotype also carried N86Y mutation. A similar pattern had been observed in parts of India [37], Asia [38,[50][51][52] and Africa [35,53,54].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Analysis indicates that 67.1% of samples with CVIET haplotype also carried N86Y mutation. A similar pattern had been observed in parts of India [37], Asia [38,[50][51][52] and Africa [35,53,54].…”
Section: Discussionsupporting
confidence: 83%
“…4). Perhaps this is because CQ (the current the treatment for P. vivax infection) could be employed for treating unrecognized mixed infections, thereby making P. falciparum vulnerable to the drug [37]. In addition, the present study on pfcrt polymorphisms indicated that CQS (41.5%) and CQR (58.5%) co-existed, albeit when CQ treatment ceased, in a manner similar to other parts of Asia [38,39] (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…Some reports have associated a rise in the prevalence of pfmdr1 86Y alleles with increasing CQ resistance [11][12]25]. The low prevalence of pfmdr1 86Y in Adamawa and Yobe raises the possibility that CQ may be effective against P. falciparum malaria in North-Eastern Nigeria once again, although this would be presumably tempered by CQ-resistance associated mutations in pfcrt, which we have not assayed here.…”
Section: Discussionmentioning
confidence: 79%
“…Mutations in PfMDR1 are associated with enhanced e ux of diverse antimalarial drugs reducing their intracellular accumulation [17,42]. Single nucleotide polymorphisms (SNPs) in pfmdr1 are associated with resistance to multiple antimalarial drugs [12,44]. Several codons in pfmdr1 have been putatively linked with changes in the parasite's sensitivity to antimalarial drugs, but codons N86Y, Y184F and D1246Y are uniquely associated with changes in artemether-lumefantrine (AL) and artesunateamodiaquine (AS-AQ) e cacies in sub-Saharan Africa [14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the risk of severe falciparum malaria would increase as the RDTs will have failed to detect P. falciparum. This fact is particularly important in malaria-endemic areas where both the circulation of chloroquine-resistant P. falciparum isolates and chloroquine is preferentially used for treating vivax malaria, as this is the case in India [56][57][58][59][60]. In most endemic countries, chloroquine is firstline treatment of vivax malaria [1].…”
Section: Discussionmentioning
confidence: 99%